Branding the University of the Philippines Mindanao College of Science and Mathematics' marang wine - Aswe, Darlene Jennifer S.
This study explores branding Marang Wine, a research output from the University of the Philippines Mindanao?s College of Science and Mathematics, with the purpose of exhibiting Marang wine to its intended market. The study was divided into three parts: Branding Elements showing the features and attributes of the wine that attracts its target market, Branding statement that defines what the brand can offer, and Package studies discussing the attempts in designing the wine package. Key informant interview with the researcher and one-shot survey with 20 respondents were done in creating a brand identity, brand image, and branding statement. A market segmentation was done in deciding the target market of the brand. The target market of the Marang wine is the young professionals that spend on outside the basic needs commodities. The proposed environment friendly and more modern design showing its characteristics and brand statement was also based on a comparative analysis of several package designs of different lambanog wines and three internationally marketed wine products.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts